PENGARUH PENAMBAHAN MASSA LILIN LEBAH (BEESWAX) SEBAGAI ZAT ANTI AIR PADA PEMBUATAN EDIBLE FILM DARI BERAS MERAH (Oryza Nivara) - Syarifuddin Oko; Andri Kurniawan; Galang Ramadhan Persada Alam (Jurnal Teknologi, 2023)
Edible film is a thin layer for food wrapping that can be made from starch. This study aims to make edible film from brown rice starch that is in accordance with the standards of the Japan Industrial Standard and has the characteristics of being resistant to water and durable as a food wrapper. Edible film in this study was made with the basic ingredients of brown rice starch as much as 10 grams with variations in the addition of beeswax as much as (1 gram, 2 grams, 3 grams, 4 grams and 5 grams). The addition of sorbitol as much as 5 grams, kesum leaf extract as much as 1.4 mL and eating vinegar as much as 10 mL. After obtaining edible film samples, several characteristic tests were carried out including tests of absorption of water, solubility in water, thickness of edible film, rate of water vapor transmission, tensile strength, and elongation. The best characteristics on edible film with the addition of beeswax 5 grams with a water absorption value of 29.15% and a solubility of 64.67% film. With a thickness value of 0.210 mm and a steam transmission rate of 1.85 gr/m2.h which is in accordance with the Japanese Industrial Standard edible film standard. However, the tensile and elongation strength values are not yet in accordance with the Japanese Industrial Standard edible film standards where the tensile strength value is 1.283 mPa and the elongation is 1.21%.